Analysis of the Implementation of Drug Control Category A with MMSL in Hospital Pharmacy Installation on Drug Values, ITOR and Stock Out - Herayanti Hermawan; Yusi Anggriani; Hesty Utami Ramadaniati; Cipto Darmodjati Kumolo (Universitas Muhammadiyah Purwokerto, 2025)
Effective drug management is crucial for enhancing both economic performance and patient health outcomes in healthcare settings. This study aims to evaluate the implementation of drug inventory control using the Minimum Maximum Stock Level (MMSL) method at Hospital “X” in Purwakarta. Employing an experimental research design, this study conducted a comparative analysis of drug consumption before and after the application of the MMSL method, focusing on key metrics such as inventory value, inventory turnover (ITOR), and stock-out rates. The study's population comprised Category A medications, totaling 106 items, with an investment value of constituting 70.6% based on ABC analysis. Data were analyzed using the Wilcoxon signed-rank test to assess the significance of the MMSL method's impact. Our findings revealed notable differences in inventory value, ITOR, and stock-out rates between the baseline consumption (Rp. 830,213,174; ITOR 2.47; stock-out Rp. 6,967,778) and the MMSL implementation period (Rp. 627,919,174; ITOR 3.15; stock-out Rp. 3,776,316), with statistical significance levels of 0.045, 0.000, and 0.300, respectively. The results indicate that the MMSL method significantly enhances drug inventory management in the hospital setting, underscoring its effectiveness in optimizing pharmaceutical resource allocation.